2006
DOI: 10.1128/aac.50.2.422-427.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Amphotericin B and Micafungin Combination on Survival, Histopathology, and Fungal Burden in Experimental Aspergillosis in the p47 phox / Mouse Model of Chronic Granulomatous Disease

Abstract: Chronic granulomatous disease (CGD) is an inherited disorder of the NADPH oxidase characterized by recurrent life-threatening bacterial and fungal infections. We characterized the effects of single and combination antifungal therapy on survival, histopathology, and laboratory markers of fungal burden in experimental aspergillosis in the p47 phox؊/؊ knockout mouse model of CGD. CGD mice were highly susceptible to intratracheal Aspergillus fumigatus challenge, whereas wild-type mice were resistant. CGD mice were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 34 publications
2
42
1
2
Order By: Relevance
“…In fact, improved efficacy has been reported in mice with chronic granulomatous disease and pulmonary aspergillosis following administration of micafungin (Mycamine) and amphotericin B (17), as well as for murine systemic aspergillosis with a combination of caspofungin plus amphotericin B or amphotericin B-intralipid (2,47). In contrast, although there was no antagonism, Clemons and Stevens (10) reported no synergistic activity of micafungin and amphotericin B for pulmonary aspergillosis in immunosuppressed DBA/2 mice.…”
mentioning
confidence: 95%
“…In fact, improved efficacy has been reported in mice with chronic granulomatous disease and pulmonary aspergillosis following administration of micafungin (Mycamine) and amphotericin B (17), as well as for murine systemic aspergillosis with a combination of caspofungin plus amphotericin B or amphotericin B-intralipid (2,47). In contrast, although there was no antagonism, Clemons and Stevens (10) reported no synergistic activity of micafungin and amphotericin B for pulmonary aspergillosis in immunosuppressed DBA/2 mice.…”
mentioning
confidence: 95%
“…AFG combined with various AMB formulations against Aspergillus spp. Although two studies suggested that there were beneficial effects from combined therapies (i.e., caspofungin plus AMB and micafungin plus AMB) over the monotherapies (11,30), most studies showed that combinations did not enhance the effects of the most active single drug (8,9,13,15,18,31). We showed that neither single drugs nor combinations were active in brain tissues.…”
mentioning
confidence: 99%
“…Dans un modèle expérimental de CGD chez la souris, l'administration endotrachéale de doses sublétales d'Aspergillus fumigatus a entraîné la formation de pyogranulomes bien circonscrits, reconnus sur des coupes histologiques de tissu pulmonaire et se distinguant des images de nécrose observées lors de neutropénies [8]. Des lésions similaires sont retrouvées dans de nombreux organes (poumons et autres tissus) chez les patients, notamment lors d'infections fongiques [9].…”
Section: Physiopathologie Des Infections Fongiques Au Cours De La Cgdunclassified
“…Par ailleurs, la sensibilité des tests microbiologiques utilisés pour le diagnostic d'une infection fongique invasive n'est pas bien définie dans le cas des patients avec CGD, et le principal marqueur utilisé pour permettre un diagnostic précoce d'aspergillose invasive, la mesure du galactomannane sérique, est très peu sensible chez ces patients [23,33]. La raison en est probablement que, contrairement aux patients neutropéniques atteints d'hémopathie maligne [33], l'aspergillose invasive chez les patients CGD n'est habituellement pas associée à une angioinvasion mais plutôt à des granulomes bien circonscrits (Figure 3) [8,9]. Les nouvelles modalités diagnostiques, comme la mesure du taux sérique de 13-D-glucane, composant de la paroi de la majorité des champignons pathogènes sauf les mucorales et Cryptococcus spp., ou l'analyse par polymerase chain reaction (PCR) d'Aspergillus (dans le sérum ou le liquide de lavage bronchoalvéolaire) n'ont pas non plus été éva-luées spécifiquement dans cette population.…”
Section: Physiopathologie Des Infections Fongiques Au Cours De La Cgdunclassified